Information System of Superior Plant Varieties - Agung Prajuhana Putra; Muchammad Isfan Noerhidayat (Journal of Science Innovare, 2023)
The Food Crops Research and Development Center and research institutes are tasked with producing high-yielding plant varieties through research within the Agricultural Research and Development Agency. The results of the technology research conducted will be promoted and disseminated to the user community which includes agricultural extension workers, academics, researchers, agribusiness entrepreneurs, policy makers, and other parties who need the information. The most effective way of distributing this technological information is by creating a website-based system so that it can be easily updated and distributed.